2015
DOI: 10.1016/j.ccl.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Management of Extracranial Carotid Artery Disease

Abstract: Stroke is the third leading cause of death in developed nations. Up to 88% of strokes are ischemic in nature. Extracranial carotid artery atherosclerotic disease is the third leading cause of ischemic stroke in the general population and the second most common non-traumatic cause among adults <45 years of age. The aim of this paper is to provide comprehensive, evidence-based recommendations for the management of extracranial atherosclerotic disease, including imaging for screening and diagnosis, medical manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 326 publications
(310 reference statements)
1
46
1
2
Order By: Relevance
“…1 Stroke is the second most common cause of death worldwide, 2 and approximately 18%-25% of all strokes are due to carotid atherosclerotic disease. 3 Conventionally, identification of atherosclerosis affecting the carotid artery is based on measurements of the degree of luminal stenosis and surface irregularities 4,5 by sonography, catheterbased angiography, and, nowadays, CTA or MRA. 6,7 However, histopathologic studies initially performed on coronary arteries and subsequently on carotid arteries demonstrate considerable differences between plaques with identical degrees of stenosis.…”
mentioning
confidence: 99%
“…1 Stroke is the second most common cause of death worldwide, 2 and approximately 18%-25% of all strokes are due to carotid atherosclerotic disease. 3 Conventionally, identification of atherosclerosis affecting the carotid artery is based on measurements of the degree of luminal stenosis and surface irregularities 4,5 by sonography, catheterbased angiography, and, nowadays, CTA or MRA. 6,7 However, histopathologic studies initially performed on coronary arteries and subsequently on carotid arteries demonstrate considerable differences between plaques with identical degrees of stenosis.…”
mentioning
confidence: 99%
“…Given the low prevalence of carotid stenosis, many organizations do not recommend screening in the general population [3][4][5]. Meanwhile, other researchers [24,25] suggested screening, especially for those with multiple risk factors for atherosclerosis, such as hypertension, hyperlipidemia, family history of atherosclerosis or ischemic stroke before 60 years of age and smoking. Jones [26] reported that the prevalence of carotid plaque was 21.0% in a total of 173 middle-aged subjects, which was similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…DSA is currently recognized as the gold standard for the diagnosis of ICA dissection and grading carotid atherosclerotic disease [5]. However, it is an invasive and high-risk procedure.…”
Section: Digital Subtraction Angiographymentioning
confidence: 99%